Chromium-zirconium-corundum refractory material, preparation method thereof and chromium-zirconium-corundum brick
By preparing chromium-zirconium corundum refractory materials with specific ratios, combined with electromelted zirconium mullite powder and synthetic chromium corundum powder, the problem of insufficient thermal shock resistance of traditional chromium-zirconium corundum refractory materials is solved, and efficient thermal shock resistance is achieved and Chemical erosion resistance.
Patent Information
- Application Number
- CN202411582339.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-07
AI Technical Summary
Traditional chromium zirconium corundum refractory materials are difficult to achieve stable and excellent thermal shock resistance while ensuring good corrosion resistance, especially in application scenarios with large temperature changes and melting kilns with large internal and external temperature differences.
By preparing a chromium zirconium corundum refractory material, a synthetic chromium corundum powder is made using a specific ratio of second chromium oxide powder and second alumina powder, and is combined with electromelted zirconium mullite powder, first chromium oxide powder and first Cooperation is carried out in the coordinated cooperation of raw materials such as alumina powder to control the Cr2O3 content of refractory materials within the range of 30% to 35%, optimize the pore distribution and improve the porosity rate.
It realizes the advantages of high porosity, high high-temperature structural strength, low high-temperature creep rate, strong chemical corrosion resistance and good thermal shock resistance of refractory materials. It is suitable for glasses with relatively large temperature deviations and high thermal shock resistance requirements. Kiln structure.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of refractory materials, and in particular to a chrome-zirconium-corundum refractory material and a preparation method thereof, and a chrome-zirconium-corundum brick. Background Art
[0002] Chrome-zirconium-corundum (Al2O3-Cr2O3 system) refractory materials have high compressive strength, flexural strength, acid and alkali corrosion resistance and chemical corrosion resistance of metal oxides. The operating temperature can reach 1800℃. They are widely used in the regenerators and walls of glass melting furnaces, lead-zinc nonferrous smelting furnaces, garbage melting furnaces, molten reduction ironmaking furnaces, carbon black reaction furnaces, water-coal slurry gasification furnaces and other parts that have strong interaction with slag.
[0003] As a hot surface lining material, due to its high service environment temperature (1300℃~1600℃), especially the large temperature fluctuations during start-up, shutdown and maintenance, higher requirements are placed on the thermal shock resistance of chromium-zirconium-corundum refractory materials. However, traditional chromium-zirconium-corundum refractory materials are difficult to achieve stable and excellent thermal shock resistance while ensuring good anti-corrosion performance, and are not suitable for application scenarios with large temperature changes and melting furnace parts with large internal and external temperature differences. Summary of the invention
[0004] Based on this, it is necessary to provide a chrome-zirconium-corundum refractory material and a preparation method thereof and a chrome-zirconium-corundum brick to solve the problem that traditional chrome-zirconium-corundum refractory materials are difficult to achieve stable and excellent thermal shock resistance while ensuring good corrosion resistance.
[0005] The above-mentioned purpose of the present application is achieved through the following technical solutions:
[0006] In a first aspect of the present application, a chrome-zirconium-corundum refractory material is provided, comprising the following raw materials in parts by weight: 50 to 80 parts of synthetic chrome-corundum powder, 6 to 16 parts of fused zirconium-mullite powder, 15 to 25 parts of a first chromium oxide powder, 6 to 12 parts of a first aluminum oxide powder, and 3 to 5 parts of a first binder;
[0007] The synthetic chromium corundum powder includes the following raw materials in parts by weight: 35 to 45 parts of second chromium oxide powder, 55 to 65 parts of second aluminum oxide powder, and 1 to 3 parts of second binder;
[0008] The synthetic chrome corundum powder includes a first synthetic chrome corundum powder with a particle size of 6-8 meshes, a second synthetic chrome corundum powder with a particle size of 8-16 meshes, a third synthetic chrome corundum powder with a particle size of 16-40 meshes, and a fourth synthetic chrome corundum powder with a particle size of ≥40 meshes;
[0009] The fused zirconium mullite powder includes a first fused zirconium mullite powder with a particle size of 1.5 mm to 3 mm and a second fused zirconium mullite powder with a particle size of 0.7 mm to 1.5 mm;
[0010] The mass fraction of Cr2O3 in the chromium-zirconium-corundum refractory material is 30%-35%.
[0011] In one embodiment, the synthetic chrome corundum powder includes the following components in parts by weight: 10 to 15 parts of a first synthetic chrome corundum powder, 10 to 20 parts of a second synthetic chrome corundum powder, 10 to 15 parts of a third synthetic chrome corundum powder, and 20 to 30 parts of a fourth synthetic chrome corundum powder.
[0012] In one embodiment, the synthetic chrome corundum powder contains the following components by mass fraction: Cr2O3 30%-35%, Al2O3 ≥58%, ZrO2 <5% and TiO2 ≤1%.
[0013] In one embodiment, the fused zirconium mullite powder comprises the following components in parts by weight: 3 to 8 parts of a first fused zirconium mullite powder and 3 to 8 parts of a second fused zirconium mullite powder.
[0014] In one embodiment, the fused zirconium mullite powder contains the following components by mass fraction: ZrO2 ≥37%, Al2O3 40%~43% and SiO2 15%~18%.
[0015] In one embodiment, the D50 particle size of the first chromium oxide powder and the second chromium oxide powder is independently 10 μm to 15 μm.
[0016] In one embodiment, the mass fraction of Cr2O3 in the first chromium oxide powder is 80%-85%.
[0017] In one embodiment, the mass fraction of Cr2O3 in the second chromium oxide powder is 70% to 80%.
[0018] In one embodiment, the first alumina powder includes alumina micro powder with a D50 particle size of 2 μm and alumina spherical powder with a D50 particle size of 10 μm to 15 μm.
[0019] In one embodiment, the second alumina powder includes alumina ball powder with a D50 particle size of 10 μm to 15 μm.
[0020] In one embodiment, the mass fraction of Al2O3 in the first alumina powder and the mass fraction of Al2O3 in the second alumina powder are each independently greater than 98.5%.
[0021] In one embodiment, the first binder and the second binder each independently include one or more of a solid binder and a liquid binder;
[0022] The solid binder comprises one or more of peach gum, gum, dextrin, lignin, lignin sulfonate, orthophosphate, condensed phosphate and carboxymethyl cellulose salt;
[0023] The liquid binder includes one or more of pulp liquid, polyvinyl alcohol solution, silica sol and water glass.
[0024] In a second aspect of the present application, a method for preparing the chromium-zirconium-corundum refractory material as described above is provided, comprising the following steps:
[0025] Preparing a molding material containing synthetic chromium corundum powder, fused zirconium mullite powder, first chromium oxide powder, first aluminum oxide powder and a first binder;
[0026] The molding material is subjected to isostatic pressing to obtain a green body;
[0027] The green body is subjected to a first sintering treatment to obtain the chromium-zirconium-corundum refractory material.
[0028] In one embodiment, the first binder includes a solid binder and a liquid binder;
[0029] The preparation method of the molding material comprises the following steps:
[0030] Mixing the first chromium oxide powder, the first aluminum oxide powder and the solid binder to obtain a powder;
[0031] Mixing the powder, the synthetic chrome corundum powder, the fused zirconium mullite powder and the liquid binder to obtain a first mixed material;
[0032] The first mixed material is subjected to drying and air-drying treatments to obtain the molding material.
[0033] In one embodiment, the method for preparing the synthetic chrome corundum powder comprises the following steps:
[0034] mixing a second chromium oxide powder, a second aluminum oxide powder, and a second binder to obtain a second mixed material;
[0035] The second mixed material is subjected to stirring milling and sand milling to obtain slurry;
[0036] The slurry is subjected to filter pressing and mud kneading and forming to obtain a mud blank;
[0037] The clay blank is subjected to a second sintering treatment and a pulverizing treatment to obtain the synthetic chrome corundum powder.
[0038] In a third aspect of the present application, a chrome-zirconium-corundum brick is provided, which is made of the chrome-zirconium-corundum refractory material as described above.
[0039] This application has at least the following beneficial effects:
[0040] The present application uses a certain ratio of second chromium oxide powder and second aluminum oxide powder to make synthetic chromium corundum powder, and cooperates with raw materials such as fused zirconium mullite powder, first chromium oxide powder and first aluminum oxide powder in a specific ratio to control the Cr2O3 content of the refractory material within the range of 30% to 35%, so that it has excellent chemical corrosion resistance. At the same time, fused zirconium mullite powder has a unique eutectic structure, as well as good high-temperature mechanical properties, high-temperature thermal properties, uniform thermal expansion, good thermal shock resistance, and excellent resistance to glass liquid corrosion, which effectively improves the erosion resistance and thermal shock resistance of the refractory material. At the same time, the use of four different particle sizes of synthetic chromium corundum powder and two different particle sizes of fused zirconium mullite powder for synergistic cooperation can achieve large and small particle grading, optimize pore distribution and increase the porosity of the granular material, thereby improving the thermal shock resistance of the refractory material. Therefore, the chromium-zirconium-corundum refractory material provided in the present application has the advantages of high porosity, high high-temperature structural strength, low high-temperature creep rate, strong resistance to chemical corrosion and good thermal shock resistance. It is suitable for glass kiln structures with relatively large temperature deviations and high requirements for thermal shock resistance. DETAILED DESCRIPTION
[0041] In order to facilitate the understanding of the present application, the present application is further described in detail below in conjunction with specific embodiments. However, the present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive.
[0042] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.
[0043] In the present application, the meaning of "and / or" includes any and all combinations of one or more related listed items. "At least one" means more than one, such as one, two and more than two. "Multiple" or "several" means at least two, such as two, three, etc., and "multi-layer" means at least two layers, such as two layers, three layers, etc., unless otherwise clearly and specifically defined. In the description of the present application, "several" means at least one, such as one, two, etc., unless otherwise clearly and specifically defined.
[0044] When a numerical range is disclosed in this application, the above range is considered to be continuous and includes the minimum and maximum values of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be combined. In other words, unless otherwise indicated, all ranges disclosed in this application should be understood to include any and all subranges included therein.
[0045] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may also include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0046] In this application, "above" or "below" includes the number itself. For example, "1 below" includes 1.
[0047] The temperature parameters in this application, unless otherwise specified, are allowed to be either constant temperature treatment or to vary within a certain temperature range. It should be understood that the constant temperature treatment allows the temperature to fluctuate within the accuracy range controlled by the instrument. Fluctuations within the range of ±5°C, ±4°C, ±3°C, ±2°C, and ±1°C are allowed.
[0048] In the present application, room temperature refers to indoor temperature, normal temperature or general temperature. Generally speaking, the range of room temperature can be any one of the following temperature intervals: 23°C ± 2°C, 25°C ± 5°C or 20°C ± 5°C.
[0049] Chrome-zirconium corundum brick, also known as chrome corundum brick, is a refractory material with a Cr2O3 content of 1%~60% (mass fraction). Its main mineral composition is α-Al2O3-Cr2O3 solid solution, and its secondary mineral composition is a small amount of composite spinel or no composite spinel. Chrome-zirconium corundum bricks are divided into two types: fused-cast chrome-zirconium corundum bricks and sintered chrome-zirconium corundum bricks. Generally, chrome-zirconium corundum bricks refer to sintered chrome-zirconium corundum bricks. The Cr2O3 content of sintered chrome-zirconium corundum bricks is usually lower than that of fused-cast chrome-zirconium corundum bricks.
[0050] There are two main methods for preparing sintered chrome-zirconium corundum bricks: one is to use α-Al2O3 powder as raw material, add appropriate amount of chromium oxide powder and chrome corundum clinker fine powder, and then sinter at high temperature after forming; the other is to use mud casting method to prepare, α-Al2O3 powder and chromium oxide powder are evenly mixed, and debonding agent and organic binder are added to make thick mud, and part of chrome corundum clinker is added at the same time, and bricks are made by grouting method, and finally sintered at high temperature. Sintered chrome-zirconium corundum bricks can be used as glass melting furnace lining, drawing glass flow hole cover bricks, and used for molten iron pretreatment equipment, garbage incinerators, water-coal slurry pressurized gasification furnace backing, etc.
[0051] In glass melting furnaces, the corrosion resistance of refractory materials is crucial. However, the Cr2O3 content in chromium-zirconium-corundum refractory materials is directly proportional to their corrosion resistance. However, the greater the Cr2O3 content, the worse the thermal shock resistance will be. It is difficult to achieve stable and excellent thermal shock resistance while ensuring good corrosion resistance.
[0052] In a first aspect, the present application provides a chrome-zirconium-corundum refractory material and a preparation method thereof and a chrome-zirconium-corundum brick to solve the problem that traditional chrome-zirconium-corundum refractory materials are difficult to achieve stable and excellent thermal shock resistance while ensuring good corrosion resistance.
[0053] In some embodiments, the chrome-zirconium-corundum refractory material includes the following raw materials in parts by weight: 50 to 80 parts of synthetic chrome-corundum powder, 6 to 16 parts of fused zirconium-mullite powder, 15 to 25 parts of first chromium oxide powder, 6 to 12 parts of first aluminum oxide powder, and 3 to 5 parts of first binder;
[0054] The synthetic chrome corundum powder includes the following raw materials in parts by weight: 35 to 45 parts of second chromium oxide powder, 55 to 65 parts of second aluminum oxide powder, and 1 to 3 parts of second binder;
[0055] The synthetic chrome corundum powder includes a first synthetic chrome corundum powder with a particle size of 6-8 meshes, a second synthetic chrome corundum powder with a particle size of 8-16 meshes, a third synthetic chrome corundum powder with a particle size of 16-40 meshes, and a fourth synthetic chrome corundum powder with a particle size of ≥40 meshes;
[0056] The fused zirconium mullite powder includes a first fused zirconium mullite powder with a particle size of 1.5 mm to 3 mm and a second fused zirconium mullite powder with a particle size of 0.7 mm to 1.5 mm;
[0057] The mass fraction of Cr2O3 in chrome-zirconium-corundum refractory is 30%~35%.
[0058] For chrome-zirconium-corundum refractory materials, there are many factors affecting their erosion resistance and thermal shock resistance, which are mainly divided into two factors: action conditions (such as temperature, temperature difference and time, etc.) and material (such as chemical composition and microstructure). Under the same action conditions, the chemical composition (such as Cr2O3 content) and microstructure (such as porosity size and distribution) of the material are mainly considered.
[0059] In terms of chemical composition, the crystal of Cr2O3 is extremely hard, with a density of 5.21g / cm 3 , melting point is 2266℃, so it can effectively improve the refractoriness of refractory materials; Cr2O3 and Al2O3 can form Al2O3-Cr2O3 continuous solid solution, improving the corrosion resistance of refractory materials; generally speaking, the higher the Cr2O3 content, the better the corrosion resistance of the refractory material, but the worse the thermal shock resistance.
[0060] In terms of porosity: refractory materials are usually composed of powder matrix and granular aggregate; the powder matrix has a higher apparent porosity, weaker erosion resistance but stronger thermal shock resistance; the granular aggregate has a dense and complete single crystal or polycrystalline structure, stronger erosion resistance but weaker thermal shock resistance.
[0061] There are reports that chrome corundum is obtained by electric arc furnace smelting and then made into chrome zirconium corundum refractory materials, but there are the following problems: the porosity of chrome zirconium corundum refractory materials is 8%-15%, which is low, resulting in a loss of thermal shock resistance; the Cr2O3 content of chrome zirconium corundum refractory materials is 6%~23%, and its corrosion resistance will be reduced; the preparation cost of chrome corundum materials by electric melting method is greatly increased.
[0062] In view of the above findings, the present application uses a certain ratio of second chromium oxide powder and second aluminum oxide powder to make synthetic chromium corundum powder, and cooperates with raw materials such as fused zirconium mullite powder, first chromium oxide powder and first aluminum oxide powder in a specific ratio to control the Cr2O3 content of the refractory material within the range of 30% to 35%, so that it has excellent chemical corrosion resistance. At the same time, fused zirconium mullite powder has a unique eutectic structure, as well as good high-temperature mechanical properties, high-temperature thermal properties, uniform thermal expansion, good thermal shock resistance, and excellent resistance to glass liquid corrosion, which effectively improves the erosion resistance and thermal shock resistance of the refractory material. At the same time, the use of four different particle sizes of synthetic chromium corundum powder and two different particle sizes of fused zirconium mullite powder for synergistic cooperation can achieve large and small particle grading, optimize pore distribution and increase the porosity of the granular material, thereby improving the thermal shock resistance of the refractory material. Therefore, the chromium-zirconium-corundum refractory material provided in the present application has the advantages of high porosity, high high-temperature structural strength, low high-temperature creep rate, strong resistance to chemical corrosion and good thermal shock resistance. It is suitable for glass kiln structures with relatively large temperature deviations and high requirements for thermal shock resistance.
[0063] As an example, in the raw materials of the chromium-zirconium-corundum refractory material, the mass portion of the synthetic chromium-corundum powder is 50 to 80 parts, for example, 50 parts, 52 parts, 55 parts, 58 parts, 60 parts, 62 parts, 65 parts, 68 parts, 70 parts, 72 parts, 75 parts, 78 parts or 80 parts, and can be further selected as 60 to 70 parts; the mass portion of the fused zirconium mullite powder is 6 to 16 parts, for example, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts or 16 parts, and can be further selected as 6 to 10 parts; the mass portion of the first chromium oxide powder is 15 parts ~25 parts, for example, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, 20 parts, 21 parts, 22 parts, 23 parts, 24 parts or 25 parts, and can be further selected as 16 parts to 20 parts; the mass portion of the first alumina powder is 6 parts to 12 parts, for example, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts or 12 parts, and can be further selected as 10 parts to 12 parts; the mass portion of the first binder is 3 parts to 5 parts, for example, 3 parts, 3.2 parts, 3.5 parts, 3.8 parts, 4 parts, 4.2 parts, 4.5 parts, 4.8 parts or 5 parts, and can be further selected as 3.5 parts to 4 parts.
[0064] As an example, in the raw material of synthetic chromium corundum powder, the mass portion of the second chromium oxide powder is 35 to 45 parts, for example, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44 or 45 parts, and can be further selected as 38 to 42 parts; the mass portion of the second aluminum oxide powder is 55 to 65 parts, for example, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64 or 65 parts, and can be further selected as 58 to 62 parts; the mass portion of the second binder is 1 to 3 parts, for example, 1, 1.2, 1.5, 1.8, 2, 2.2, 2.5, 2.8 or 3 parts, and can be further selected as 2 parts.
[0065] As an example, in the components of synthetic chrome corundum powder, the particle size of the first synthetic chrome corundum powder is 6 mesh to 8 mesh (i.e., 1875 μm to 2500 μm), such as 6 mesh, 6.5 mesh, 7 mesh, 7.5 mesh or 8 mesh; the particle size of the second synthetic chrome corundum powder is 8 mesh to 16 mesh (i.e., 937.5 μm to 1875 μm), such as 8 mesh, 9 mesh, 10 mesh, 11 mesh, 12 mesh, 13 mesh, 14 mesh, 15 mesh or 16 mesh; the particle size of the third synthetic chrome corundum powder is 8 mesh to 16 mesh (i.e., 937.5 μm to 1875 μm), such as 8 mesh, 9 mesh, 10 mesh, 11 mesh, 12 mesh, 13 mesh, 14 mesh, 15 mesh or 16 mesh; The particle size is 16 mesh ~ 40 mesh (i.e. 375μm ~ 937.5μm), for example, 16 mesh, 18 mesh, 20 mesh, 22 mesh, 24 mesh, 26 mesh, 28 mesh, 30 mesh, 32 mesh, 34 mesh, 36 mesh, 38 mesh or 40 mesh; the particle size of the fourth synthetic chromium corundum powder is ≥40 mesh (i.e. ≤375μm), for example, 40 mesh, 50 mesh, 60 mesh, 70 mesh, 80 mesh, 90 mesh, 100 mesh, 150 mesh, 200 mesh or 325 mesh.
[0066] Optionally, the synthetic chrome corundum powder includes the following components in parts by mass: 10 to 15 parts of a first synthetic chrome corundum powder, 10 to 20 parts of a second synthetic chrome corundum powder, 10 to 15 parts of a third synthetic chrome corundum powder, and 20 to 30 parts of a fourth synthetic chrome corundum powder.
[0067] As an example, in the components of synthetic chromium corundum powder, the mass portion of the first synthetic chromium corundum powder is 10 parts to 15 parts, such as 10 parts, 11 parts, 12 parts, 13 parts, 14 parts or 15 parts, and further optionally 10 parts to 12 parts; the mass portion of the second synthetic chromium corundum powder is 10 parts to 20 parts, such as 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts or 20 parts, and further optionally The mass portion of the third synthetic chromium corundum powder is 10 to 15 parts, for example, 10, 11, 12, 13, 14 or 15 parts, and can be further selected as 10 to 12 parts; the mass portion of the fourth synthetic chromium corundum powder is 20 to 30 parts, for example, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29 or 30 parts, and can be further selected as 27 to 30 parts.
[0068] By adjusting the dosage of four synthetic chrome corundum powders with different particle sizes, the large and small particles of the synthetic chrome corundum powder can be reasonably matched, and the size and distribution uniformity of the pores can be optimized, thereby ensuring that the refractory material has a higher porosity and better thermal shock resistance.
[0069] Optionally, the synthetic chrome corundum powder contains the following components by mass fraction: Cr2O3 30%-35%, Al2O3 ≥58%, ZrO2 <5% and TiO2 ≤1%.
[0070] By controlling the Cr2O3 content and Al2O3 content in synthetic chrome corundum powder and combining the ratio of synthetic chrome corundum powder and other raw materials, the Cr2O3 content in the refractory material can be precisely controlled, thereby ensuring that the refractory material has stable and excellent resistance to chemical corrosion.
[0071] As an example, in the fused zirconium mullite powder, the particle size of the first fused zirconium mullite powder is 1.5mm~3mm, for example, 1.5mm, 1.6mm, 1.7mm, 1.8mm, 1.9mm, 2mm, 2.1mm, 2.2mm, 2.3mm, 2.4mm, 2.5mm, 2.6mm, 2.7mm, 2.8mm, 2.9mm or 3mm; the particle size of the second fused zirconium mullite powder is 0.7mm~1.5mm, for example, 0.7mm, 0.8mm, 0.9mm, 1mm, 1.1mm, 1.2mm, 1.3mm, 1.4mm or 1.5mm.
[0072] Optionally, the fused zirconium mullite powder comprises the following components in parts by mass: 3 parts to 8 parts of the first fused zirconium mullite powder and 3 parts to 8 parts of the second fused zirconium mullite powder.
[0073] As an example, in the components of fused zirconium mullite powder, the mass proportion of the first fused zirconium mullite powder is 3 to 8 parts, for example, 3, 4, 5, 6, 7 or 8 parts, and can be further selected as 3 to 5 parts; the mass proportion of the second fused zirconium mullite powder is 3 to 8 parts, for example, 3, 4, 5, 6, 7 or 8 parts, and can be further selected as 3 to 5 parts.
[0074] By regulating the dosage of two fused zirconium mullite powders with different particle sizes, the large and small particles of the fused zirconium mullite powder can be reasonably matched, and the size and distribution uniformity of the pores can be optimized, thereby ensuring that the refractory material has a higher porosity and better thermal shock resistance.
[0075] Optionally, the fused zirconium mullite powder contains the following components by mass fraction: ZrO2 ≥37%, Al2O3 40%~43% and SiO2 15%~18%.
[0076] By controlling the ZrO2 content and Al2O3 content in the fused zirconium mullite powder and combining the ratio of the fused zirconium mullite powder and other raw materials, the ZrO2 content in the refractory material can be precisely controlled, thereby ensuring that the refractory material has stable and excellent thermal shock resistance.
[0077] Optionally, the D50 particle size of the first chromium oxide powder and the second chromium oxide powder is independently 10 μm to 15 μm, for example, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm or 15 μm.
[0078] Optionally, the mass fraction of Cr2O3 in the first chromium oxide powder is 80% to 85%, such as 80%, 81%, 82%, 83%, 84% or 85%. Further optionally, the first chromium oxide powder is a chromium oxide ball powder, which contains the following components in mass fractions: Cr2O3 80% to 85%, Al2O3 ≥10%, ZrO2 <5% and TiO2 ≤2%.
[0079] Optionally, the mass fraction of Cr2O3 in the second chromium oxide powder is 70% to 80%, such as 70%, 71%, 72%, 73%, 74%, 75%, 76%, 77%, 78%, 79% or 80%. Further optionally, the second chromium oxide powder is chromium oxide sludge, which contains the following components in mass fractions: Cr2O3 70% to 80%, Al2O3 ≥10%, ZrO2 <10% and TiO2 ≤1.5%.
[0080] Optionally, the first alumina powder includes alumina micro powder with a D50 particle size of 2 μm and alumina spherical powder with a D50 particle size of 10 μm to 15 μm.
[0081] Optionally, the second alumina powder includes alumina ball powder with a D50 particle size of 10 μm to 15 μm.
[0082] The alumina micropowder includes α-Al2O3 micropowder, and the alumina spherical powder includes plate-like corundum spherical powder.
[0083] Optionally, the mass fraction of Al2O3 in the first alumina powder and the mass fraction of Al2O3 in the second alumina powder are each independently >98.5%. Further optionally, the first alumina powder and the second alumina powder contain the following components in mass fractions: Al2O3 >98.5% and SiO2 <0.1%.
[0084] Optionally, the first binder and the second binder each independently include one or more of a solid binder and a liquid binder;
[0085] The solid binder comprises one or more of peach gum, gum, dextrin, lignin, lignin sulfonate, orthophosphate, condensed phosphate and carboxymethyl cellulose salt;
[0086] The liquid binder includes one or more of pulp liquid, polyvinyl alcohol solution, silica sol and water glass.
[0087] It is understandable that the first binder and the second binder can be mixed with other raw materials in solid and / or liquid form. The solid binder and liquid binder selected in the present application have good cold and hot bonding strengths, can glue together bulk raw materials of different particle sizes, facilitate subsequent molding and high-temperature sintering, and are conducive to improving the strength and plasticity of refractory materials.
[0088] Among them, lignin sulfonate is an industrial raw material for the recovery and extraction of sulfite pulping and papermaking waste liquid, which can be sodium lignin sulfonate, calcium lignin sulfonate or ammonium lignin sulfonate. Orthophosphate can be used as a binder for neutral refractory materials and acidic refractory materials, mainly dihydrogen phosphate and monohydrogen phosphate, such as aluminum dihydrogen phosphate (Al (H2PO4)5, ADP). Carboxymethyl cellulose salt can be sodium carboxymethyl cellulose or potassium carboxymethyl cellulose.
[0089] As an example, the mass fraction of Cr2O3 in the chrome-zirconium-corundum refractory material is 30%~35%, for example, 30%, 30.5%, 31%, 31.5%, 32%, 32.5%, 33%, 33.5%, 34%, 34.5% or 35%, and can be further optionally 30%~32.5%.
[0090] Optionally, the porosity of the chromium-zirconium-corundum refractory material is 15% to 18%, such as 15%, 15.5%, 16%, 16.5%, 17%, 17.5% or 18%, and can further be 15.8% to 17.4%.
[0091] Optionally, the volume density of the chromium zirconium corundum refractory material is 3.4 g / cm 3 ~3.5g / cm 3 , for example 3.4g / cm 3 、3.41g / cm 3 、3.42g / cm 3 、3.43g / cm 3 、3.44g / cm 3 、3.45g / cm 3 、3.46g / cm 3 、3.47g / cm 3 、3.48g / cm 3 、3.49g / cm 3 or 3.5g / cm 3 , further optional to 3.41g / cm 3 ~3.46g / cm 3 .
[0092] Optionally, the thermal shock resistance of the chromium-zirconium-corundum refractory material is ≥30 times.
[0093] In a second aspect of the present application, a method for preparing the chromium-zirconium-corundum refractory material as described above is provided, comprising the following steps:
[0094] S100: preparing a molding material containing synthetic chromium corundum powder, fused zirconium mullite powder, a first chromium oxide powder, a first aluminum oxide powder and a first binder;
[0095] S200: isostatically pressing the molding material to obtain a green body;
[0096] S300: performing a first sintering treatment on the green body to obtain a chromium-zirconium-corundum refractory material.
[0097] Optionally, the first firing treatment is carried out in a tunnel kiln; the firing temperature of the first firing treatment is 1610°C~1630°C, for example, 1610°C, 1615°C, 1620°C, 1625°C or 1630°C; the insulation time of the first firing treatment is 10h~12h, for example, 10h, 10.5h, 11h, 11.5h or 12h.
[0098] Optionally, the first binder includes a solid binder and a liquid binder;
[0099] The preparation method of the molding material comprises the following steps:
[0100] S111: mixing a first chromium oxide powder, a first aluminum oxide powder and a solid binder to obtain a powder;
[0101] S112: mixing powder, synthetic chrome corundum powder, fused zirconium mullite powder and liquid binder to obtain a first mixture;
[0102] S113: drying and cooling the first mixed material to obtain a molding material.
[0103] Further optionally, the method for preparing the molding material comprises the following steps:
[0104] S111: putting the first chromium oxide powder, the first aluminum oxide powder and the solid binder into a conical mixer and mixing for 2 hours to obtain a powder;
[0105] S112: putting synthetic chrome corundum powder and fused zirconium mullite powder into a wet mill, adding a liquid binder, mixing for about 6 minutes, then adding powder, mixing for about 10 minutes, to obtain a first mixed material with a water content of 1.0wt% to 1.5wt.%;
[0106] S113: Dry the first mixed material to a moisture content of ≤0.48wt.%, and place it to dry below room temperature to obtain a molding material.
[0107] Optionally, the preparation method of synthetic chrome corundum powder comprises the following steps:
[0108] S121: mixing a second chromium oxide powder, a second aluminum oxide powder, and a second binder to obtain a second mixture;
[0109] S122: performing stirring milling and sand milling on the second mixed material to obtain slurry;
[0110] S123: performing filter pressing and mud kneading and forming on the slurry to obtain a mud blank;
[0111] S124: subjecting the clay to a second sintering treatment and a pulverizing treatment to obtain synthetic chrome corundum powder.
[0112] Optionally, the stirred mill treatment includes the following steps: adding water to the second mixture, starting the stirred mill to mix the materials, then starting the circulation pump, discharging the materials, pumping the slurry into a slurry storage barrel, and adding an appropriate amount of water to flush the residual materials in the pipeline into the slurry storage barrel to obtain slurry.
[0113] Optionally, the sand grinding treatment includes the following steps: stirring the slurry in the slurry storage barrel evenly, discharging the slurry into a sand mill, cyclically sand grinding for 3 to 5 times, discharging the material into a slurry storage mixing tank, and obtaining mud with a D50 particle size of 2.0 μm to 3.5 μm.
[0114] Optionally, the mud is subjected to filter pressing and mud kneading and molding treatment, comprising the following steps: transferring the mud in the slurry storage mixing tank to a filter press for filter pressing treatment to obtain a mud cake; transferring the mud cake to a mud kneading machine for mud kneading and molding treatment, and then placing it to dry below room temperature to obtain a mud blank.
[0115] Optionally, the second firing treatment is carried out in a tunnel kiln; the firing temperature of the second firing treatment is 1620°C to 1670°C, for example, 1620°C, 1630°C, 1640°C, 1650°C, 1660°C or 1670°C; the insulation time of the second firing treatment is 10h to 12h, for example, 10h, 10.5h, 11h, 11.5h or 12h.
[0116] Optionally, the pulverizing process is performed by a crushing double-roller machine; after the pulverizing, a screening process is performed to obtain synthetic chrome corundum powders of different particle sizes; after the screening, an iron removal process can also be performed to obtain synthetic chrome corundum powders that meet the composition requirements and particle size requirements.
[0117] The chromium-zirconium-corundum refractory material provided in the present application can be smelted without using an electric arc furnace, but various raw materials can be pressed into shape and sintered at high temperature, which is beneficial for optimizing the pore distribution and increasing the porosity, thereby improving the thermal shock resistance of the refractory material, and is also beneficial for reducing the preparation cost.
[0118] In a third aspect of the present application, a chrome-zirconium-corundum brick is provided, which is made of the chrome-zirconium-corundum refractory material as described above.
[0119] It can be understood that the chrome-zirconium corundum brick material is made of the chrome-zirconium corundum refractory material as described above, because it also has the advantages of high porosity, high high-temperature structural strength, low high-temperature creep rate, strong resistance to chemical corrosion and good thermal shock resistance. It is suitable for use as refractory bricks in the heat storage chamber and walls of glass kilns. It is also suitable for use in lead-zinc non-ferrous smelting furnaces, garbage melting furnaces, molten reduction ironmaking furnaces, carbon black reaction furnaces, water-coal slurry gasification furnaces and other parts that have strong interactions with slag.
[0120] The following is further described in conjunction with specific examples and comparative examples. The raw materials involved in the following specific examples and comparative examples, unless otherwise specified, can all be sourced from commercial sources, the instruments used, unless otherwise specified, can all be sourced from commercial sources, and the processes involved, unless otherwise specified, are all conventionally selected by those skilled in the art. Among them, some raw materials are shown in Table 1:
[0121] Table 1. Raw materials in Examples and Comparative Examples
[0122]
[0123] Note: (1) Chromium oxide ball powder: chromium oxide green and α-Al2O3 powder are mixed in a mass ratio of (80-85): (15-20), calcined in a tunnel kiln at 1620°C and then ground into powder; (2) Chromium oxide mud A and chromium oxide mud B: The leftover scraps after processing the commercially available products of Guangdong Xinlingnan Technology Co., Ltd. are dried and ground into powder.
[0124] Example 1
[0125] (i) Referring to Table 2, the chromium-zirconium-corundum refractory material of this embodiment includes the following raw materials in parts by weight: 62 parts of synthetic chromium-corundum powder, 8 parts of fused zirconium-mullite powder, 18 parts of first chromium oxide powder, 12 parts of first aluminum oxide powder, and 3.9 parts of first binder;
[0126] Synthetic chrome corundum powder: 10 parts of the first synthetic chrome corundum powder, 14 parts of the second synthetic chrome corundum powder, 10 parts of the third synthetic chrome corundum powder, and 28 parts of the fourth synthetic chrome corundum powder;
[0127] Fused zirconium mullite powder: 4 parts of first fused zirconium mullite powder and 4 parts of second fused zirconium mullite powder;
[0128] First chromium oxide powder: 18 parts of chromium oxide ball powder;
[0129] First alumina powder: 6 parts of α-Al2O3 powder and 6 parts of plate-like corundum ball powder;
[0130] The first binder: 1.5 parts of solid binder (peach gum powder) and 2.4 parts of liquid binder (polyvinyl alcohol aqueous solution).
[0131] (II) Please refer to Table 3. The synthetic chrome corundum powder includes the following raw materials in parts by weight:
[0132] 42 parts of second chromium oxide powder, 58 parts of second aluminum oxide powder and 2 parts of second binder; wherein, the second chromium oxide powder is chromium oxide mud B, the second aluminum oxide powder is plate-like corundum ball powder, and the second binder is a solid binder (dextrin powder).
[0133] (III) The preparation method of the chromium-zirconium-corundum refractory material of this embodiment is as follows:
[0134] (1) Preparation of synthetic chrome corundum powder:
[0135] mixing a second chromium oxide powder, a second aluminum oxide powder, and a second binder to obtain a second mixed material;
[0136] Add water to the second mixed material, start the stirring mill to mix the materials, then start the circulation pump, discharge the materials, pump the slurry into the slurry storage barrel, and add an appropriate amount of water to flush the residual materials in the pipeline into the slurry storage barrel to obtain slurry;
[0137] The slurry in the slurry storage barrel is stirred evenly, and the slurry is discharged into the sand mill, and the slurry is circulated and sand milled for 3 to 5 times, and the slurry is discharged into the slurry storage mixing tank to obtain the slurry with a D50 particle size of 2.0 μm to 3.5 μm;
[0138] The slurry in the slurry storage and mixing tank is transferred to a filter press for filter pressing to obtain a mud cake; the mud cake is transferred to a mud kneading machine for mud kneading and molding, and then placed to dry to below room temperature to obtain a mud blank;
[0139] The clay blank is transferred to a tunnel kiln and kept at a firing temperature of 1670°C for 12 hours; it is taken out after cooling in the furnace and crushed by a crushing double-roller mill, and then sieved and iron-removed to obtain a first synthetic chrome corundum powder, a second synthetic chrome corundum powder, a third synthetic chrome corundum powder and a fourth synthetic chrome corundum powder.
[0140] (2) Preparing a molding material: putting a first chromium oxide powder, a first aluminum oxide powder and a solid binder into a conical mixer and mixing for 2 hours to obtain a powder; putting synthetic chromium corundum powder and fused zirconium mullite powder into a wet mill, adding a liquid binder, mixing for about 6 minutes, and then adding the powder, mixing for about 10 minutes to obtain a first mixed material with a moisture content of 1.0wt%~1.5wt.%; drying the first mixed material to a moisture content of ≤0.48wt.%, and leaving it to dry to below room temperature to obtain a molding material.
[0141] (3) Preparing a green body: subjecting the molding material to isostatic pressing to obtain a green body;
[0142] (4) Preparation of chrome-zirconium corundum bricks: The green body is transferred to a tunnel kiln and kept at a firing temperature of 1620°C for 16 hours to obtain a chrome-zirconium corundum refractory material; after cooling in the furnace, the green body is taken out, cut and drilled to obtain a chrome-zirconium corundum brick.
[0143] Embodiments 2 to 10
[0144] Embodiments 2 to 10 are substantially the same as Embodiment 1, except that:
[0145] Example 2: The first binder is selected from 1.5 parts of a solid binder (aluminum dihydrogen phosphate ADP) and 2.4 parts of a liquid binder (polyvinyl alcohol aqueous solution).
[0146] Embodiment 3: The first binder is selected from 1.5 parts of solid binder (peach gum powder) and 2.1 parts of liquid binder (polyvinyl alcohol aqueous solution).
[0147] Example 4: Synthetic chrome corundum powder includes 10 parts of first synthetic chrome corundum powder, 14 parts of second synthetic chrome corundum powder, 10 parts of third synthetic chrome corundum powder and 26 parts of fourth synthetic chrome corundum powder, and fused zirconium mullite powder: 6 parts of first fused zirconium mullite powder and 4 parts of second fused zirconium mullite powder.
[0148] Example 5: Synthetic chrome corundum powder includes 10 parts of first synthetic chrome corundum powder, 16 parts of second synthetic chrome corundum powder, 10 parts of third synthetic chrome corundum powder and 28 parts of fourth synthetic chrome corundum powder, and fused zirconium mullite powder: 2 parts of first fused zirconium mullite powder and 4 parts of second fused zirconium mullite powder.
[0149] Example 6: The synthetic chrome corundum powder includes 14 parts of the first synthetic chrome corundum powder, 10 parts of the second synthetic chrome corundum powder, 14 parts of the third synthetic chrome corundum powder, and 24 parts of the fourth synthetic chrome corundum powder;
[0150] Example 7: The synthetic chrome corundum powder includes 18 parts of the first synthetic chrome corundum powder, 12 parts of the second synthetic chrome corundum powder, 12 parts of the third synthetic chrome corundum powder, and 20 parts of the fourth synthetic chrome corundum powder;
[0151] Example 8: The synthetic chrome corundum powder includes 12 parts of the first synthetic chrome corundum powder, and the fused zirconium mullite powder includes 3 parts of the first fused zirconium mullite powder and 3 parts of the second fused zirconium mullite powder;
[0152] Example 9: The fused zirconium mullite powder includes 8 parts of a first fused zirconium mullite powder and 8 parts of a second fused zirconium mullite powder;
[0153] Example 10: Synthetic chromium corundum powder includes 38 parts of second chromium oxide powder, 62 parts of second aluminum oxide powder and 2 parts of second binder; wherein, the second chromium oxide powder is chromium oxide mud B, the second aluminum oxide powder is plate-like corundum ball powder, and the second binder is a solid binder (dextrin powder).
[0154] Comparative Example 1
[0155] (i) Referring to Table 2, the chromium-zirconium-corundum refractory material of this comparative example includes the following raw materials in parts by weight: 62 parts of synthetic chromium-corundum powder, 8 parts of fused zirconium-mullite powder, 26.7 parts of first chromium oxide powder, 3.3 parts of first aluminum oxide powder, and 3.9 parts of first binder;
[0156] Synthetic chrome corundum powder: 18 parts of the first synthetic chrome corundum powder, 10 parts of the second synthetic chrome corundum powder, 8 parts of the third synthetic chrome corundum powder, and 26 parts of the fourth synthetic chrome corundum powder;
[0157] Fused zirconium mullite powder: 8 parts of first fused zirconium mullite powder;
[0158] First chromium oxide powder: 19.5 parts of chromium oxide mud A and 7.2 parts of chromium oxide green;
[0159] First alumina powder: 1.8 parts of α-Al2O3 powder and 1.5 parts of plate-like corundum ball powder;
[0160] The first binder: 1.5 parts of solid binder (peach gum powder) and 2.4 parts of liquid binder (polyvinyl alcohol aqueous solution).
[0161] (ii) Formula of synthetic chrome corundum powder: same as that in Example 1.
[0162] (III) Preparation method of chromium-zirconium corundum bricks: same as in Example 1.
[0163] Comparative Example 2
[0164] (I) Referring to Table 2, the chromium-zirconium-corundum refractory material of this comparative example includes the following raw materials in parts by weight: 67 parts of synthetic chromium-corundum powder, 15.5 parts of first chromium oxide powder, 17.5 parts of first aluminum oxide powder, and 3.7 parts of first binder;
[0165] Synthetic chrome corundum powder: 10 parts of the first synthetic chrome corundum powder, 20 parts of the second synthetic chrome corundum powder, 13 parts of the third synthetic chrome corundum powder, and 24 parts of the fourth synthetic chrome corundum powder;
[0166] First chromium oxide powder: 15.5 parts of chromium oxide ball powder;
[0167] First alumina powder: 6.6 parts of α-Al2O3 powder and 10.9 parts of plate-like corundum ball powder;
[0168] The first binder: 1.5 parts of solid binder (peach gum powder) and 2.2 parts of liquid binder (polyvinyl alcohol aqueous solution).
[0169] (ii) Formula of synthetic chrome corundum powder: same as that in Example 1.
[0170] (III) Preparation method of chromium-zirconium corundum bricks: same as in Example 1.
[0171] Comparative Examples 3~6
[0172] Comparative Examples 3-4 are substantially the same as Example 1, except that:
[0173] Comparative Example 3: The synthetic chrome corundum powder includes 31 parts of the first synthetic chrome corundum powder and 31 parts of the second synthetic chrome corundum powder;
[0174] Comparative Example 4: The synthetic chrome corundum powder includes 31 parts of the third synthetic chrome corundum powder and 31 parts of the fourth synthetic chrome corundum powder;
[0175] Comparative Example 5: The fused zirconium mullite powder is selected from 8 parts of the first fused zirconium mullite powder;
[0176] Comparative Example 6: The fused zirconium mullite powder is 8 parts of the second fused zirconium mullite powder.
[0177] Test Case
[0178] The chromium-zirconium-corundum bricks of each embodiment and each comparative example were tested as follows, and the results are shown in Table 4.
[0179] (1) Cr2O3 content test: refer to "GB / T 21114-2019 Refractory Materials X-ray Fluorescence Spectrochemical Analysis Cast Glass Plate Method" for testing.
[0180] (2) Porosity and bulk density: Test according to GB / T 2997-2015 Test method for bulk density, apparent porosity and true porosity of dense shaped refractory products.
[0181] (3) Thermal shock resistance: Refer to GB / T 30873-2014 Test method for thermal shock resistance of refractory materials to test the number of rapid heating and cooling cycles experienced when the heated end face of the test sample is half damaged; the more thermal shocks, the better the thermal shock resistance. Refer to DIN51068:2008 Test of ceramic raw materials and basic materials. Determination of thermal shock resistance. Method for quenching refractory bricks with water, and use the electric furnace of Tianjin Scientific Instruments and Equipment Factory to test the number of thermal shocks when visible cracks appear in electrode bricks; the more thermal shocks, the better the thermal shock resistance of electrode bricks.
[0182] (4) Glass liquid erosion test: Referring to JC / T 806-2013 Test method for static glass liquid erosion resistance of refractory materials for glass melting furnaces, the chrome-zirconium corundum bricks were made into strip samples for use, and a block of test glass was added to a crucible, and the crucible was placed in a high-temperature electric furnace for heating to melt the test glass into glass liquid. The chrome-zirconium corundum strip sample was then inserted into the test glass, and the crucible was rotated. The erosion test was carried out at 1570°C for 72 hours. After the test, the unidirectional erosion amount of the strip sample at the liquid surface and 1 / 2 below the liquid surface was measured using a Leica S6D stereo microscope. The total erosion amount and the unit total time were calculated to obtain the erosion amount of the chrome-zirconium corundum brick per unit time (mm / 24h). By comparing the unit erosion amount, its excellent erosion resistance was obtained. Among them, the test glass was microcrystalline glass (Wenzhou Kanger Microcrystalline Co., Ltd.); the flow rate of the glass liquid was 45m / h.
[0183] It can be seen from Table 4 that the chromium-zirconium corundum bricks of Examples 1 to 10 have an average Cr2O3 content of 30.42% to 32.43%, an average porosity of 15.9% to 18.4%, and an average bulk density of 3.39 g / cm 3 ~3.45g / cm 3, the number of thermal shock resistance is >30 times, the unidirectional erosion at the liquid surface is ≤0.060mm / 24h, and the unidirectional erosion at 1 / 2 below the liquid surface is ≤0.040mm / 24h, which shows that the introduction of fused zirconium mullite powder of different particle sizes into the chrome-zirconium corundum brick and the combination with synthetic chrome corundum powder of different particle sizes can effectively improve the thermal shock resistance of the product while maintaining good erosion resistance, and can achieve better results under appropriate particle grading. In this case, the slight change in particle composition has little effect on its thermal shock resistance. From Examples 5 to 6 and 8 to 9, the increase in the amount of fused zirconium mullite powder leads to an increase in the unidirectional erosion at the liquid surface and 1 / 2 below the liquid surface, indicating that the introduction of fused zirconium mullite aggregate will sacrifice some erosion resistance, and the erosion resistance of the homogeneous chrome-zirconium corundum brick with the same chromium content will be slightly worse, but the impact is not large.
[0184] In Comparative Example 2, no fused zirconium mullite powder was added, and the thermal shock resistance was very poor. In Comparative Example 1 and Comparative Example 5, only the first fused zirconium mullite powder (1.5mm~3mm) was added, resulting in a decrease in thermal shock resistance and erosion resistance; in Comparative Example 6, only the second fused zirconium mullite powder (0.7mm~1.5mm) was added, resulting in a decrease in thermal shock resistance; in Comparative Example 3, only the first synthetic chromium corundum powder (6 mesh~8 mesh) and the second synthetic chromium corundum powder (8 mesh~16 mesh) were added, and in Comparative Example 4, only the third synthetic chromium corundum powder (particle size of 16 mesh~40 mesh) and the fourth synthetic chromium corundum powder (particle size ≥40 mesh) were added, resulting in a decrease in thermal shock resistance and erosion resistance. It is proved that the combination of fused zirconium mullite powder and synthetic chromium corundum powder of different particle sizes can form the effect of large and small particle grading, optimize the pore distribution and increase the porosity, thereby improving the thermal shock resistance while maintaining good chemical corrosion resistance.
[0185] Table 2. Formula of chromium-zirconium-corundum refractory material (unit: mass parts)
[0186]
[0187] Table 3. Formula of synthetic chrome corundum powder (unit: mass parts)
[0188]
[0189] Table 4. Properties of chrome-zirconium corundum bricks
[0190]
[0191] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0192] The above-described embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of protection of the present application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the scope of protection of the present application. Therefore, the scope of protection of the present application shall be subject to the attached claims.
Claims
1. A chromium-zirconium-corundum refractory material, characterized in that: The raw materials include the following parts by weight: 50 to 80 parts of synthetic chromium corundum powder, 6 to 16 parts of fused zirconium mullite powder, 15 to 25 parts of first chromium oxide powder, 6 to 12 parts of first aluminum oxide powder and 3 to 5 parts of first binder; The synthetic chromium corundum powder includes the following raw materials in parts by weight: 35 to 45 parts of second chromium oxide powder, 55 to 65 parts of second aluminum oxide powder, and 1 to 3 parts of second binder; The synthetic chrome corundum powder includes a first synthetic chrome corundum powder with a particle size of 6-8 meshes, a second synthetic chrome corundum powder with a particle size of 8-16 meshes, a third synthetic chrome corundum powder with a particle size of 16-40 meshes, and a fourth synthetic chrome corundum powder with a particle size of ≥40 meshes; The fused zirconium mullite powder includes a first fused zirconium mullite powder with a particle size of 1.5 mm to 3 mm and a second fused zirconium mullite powder with a particle size of 0.7 mm to 1.5 mm; The mass fraction of Cr2O3 in the chromium-zirconium-corundum refractory material is 30%-35%.
2. The chromium-zirconium-corundum refractory material according to claim 1, characterized in that: The synthetic chrome corundum powder includes the following components in parts by mass: 10 to 15 parts of a first synthetic chrome corundum powder, 10 to 20 parts of a second synthetic chrome corundum powder, 10 to 15 parts of a third synthetic chrome corundum powder, and 20 to 30 parts of a fourth synthetic chrome corundum powder.
3. The chromium-zirconium-corundum refractory material according to claim 2, characterized in that: The synthetic chrome corundum powder contains the following components by mass fraction: Cr2O3 30%-35%, Al2O3 ≥58%, ZrO2 <5% and TiO2 ≤1%.
4. The chromium-zirconium-corundum refractory material according to claim 1, characterized in that: The fused zirconium mullite powder comprises the following components in parts by weight: 3 to 8 parts of a first fused zirconium mullite powder and 3 to 8 parts of a second fused zirconium mullite powder.
5. The chromium-zirconium-corundum refractory material according to claim 4, characterized in that: The fused zirconium mullite powder contains the following components by mass fraction: ZrO2 ≥37%, Al2O3 40%-43% and SiO2 15%-18%.
6. The chromium-zirconium-corundum refractory material according to any one of claims 1 to 5, characterized in that: One or more of the following conditions are met: (1) The D50 particle size of the first chromium oxide powder and the second chromium oxide powder is independently 10 μm to 15 μm; (2) The mass fraction of Cr2O3 in the first chromium oxide powder is 80% to 85%; (3) The mass fraction of Cr2O3 in the second chromium oxide powder is 70% to 80%.
7. The chromium-zirconium-corundum refractory material according to any one of claims 1 to 5, characterized in that: One or more of the following conditions are met: (1) The first alumina powder includes alumina micropowder with a D50 particle size of 2 μm and alumina spherical powder with a D50 particle size of 10 μm to 15 μm; (2) The second alumina powder comprises alumina ball powder with a D50 particle size of 10 μm to 15 μm; (3) The mass fraction of Al2O3 in the first alumina powder and the mass fraction of Al2O3 in the second alumina powder are each independently greater than 98.5%.
8. The chromium-zirconium-corundum refractory material according to any one of claims 1 to 5, characterized in that: The first binder and the second binder each independently include one or more of a solid binder and a liquid binder; The solid binder comprises one or more of peach gum, gum, dextrin, lignin, lignin sulfonate, orthophosphate, condensed phosphate and carboxymethyl cellulose salt; The liquid binder includes one or more of pulp liquid, polyvinyl alcohol solution, silica sol and water glass.
9. A method for preparing a chromium-zirconium-corundum refractory material according to any one of claims 1 to 8, characterized in that: The following steps are involved: Preparing a molding material containing synthetic chromium corundum powder, fused zirconium mullite powder, first chromium oxide powder, first aluminum oxide powder and a first binder; The molding material is subjected to isostatic pressing to obtain a green body; The green body is subjected to a first sintering treatment to obtain the chromium-zirconium-corundum refractory material.
10. The method for preparing the chromium-zirconium-corundum refractory material according to claim 9, characterized in that: The first binder includes a solid binder and a liquid binder; The preparation method of the molding material comprises the following steps: Mixing the first chromium oxide powder, the first aluminum oxide powder and the solid binder to obtain a powder; Mixing the powder, the synthetic chrome corundum powder, the fused zirconium mullite powder and the liquid binder to obtain a first mixed material; The first mixed material is subjected to drying and air-drying treatments to obtain the molding material.
11. The method for preparing a chromium-zirconium-corundum refractory material according to claim 9, characterized in that: The preparation method of the synthetic chrome corundum powder comprises the following steps: mixing a second chromium oxide powder, a second aluminum oxide powder, and a second binder to obtain a second mixed material; The second mixed material is subjected to stirring milling and sand milling to obtain slurry; The slurry is subjected to filter pressing and mud kneading and forming to obtain a mud blank; The clay blank is subjected to a second sintering treatment and a pulverizing treatment to obtain the synthetic chrome corundum powder.
12. A chrome-zirconium corundum brick, characterized in that: It is made of the chromium-zirconium-corundum refractory material as described in any one of claims 1 to 8.
Citation Information
Patent Citations
Cr2O3-Al2O3 refractory material of anisotropic structure
CN102417361A
Chromium zirconium corundum aggregate, mixed active powder, chromium zirconium corundum composite material, and preparation method thereof
CN106187125A
Sintered aluminum-chromium-zirconium sliding plate brick for copper smelting anode furnace and preparation method of sintered aluminum-chromium-zirconium sliding plate brick
CN110746180A
Chromium-zirconium-corundum aggregate and preparation method thereof, chromium-zirconium-corundum composite material and preparation method and application thereof
CN117003569A
Refractory material based on chromium corundum, a chromium corundum brick and the use of said brick
US6352951B1
Cited By
High-alumina refractory material as well as preparation method and application thereof
CN121342489A
High-alumina refractory material, method for preparing same, and use thereof
CN121342489B